Effect of coral aggregates of blended cement concrete subjected to different water immersion condition - Bunyamin, Bunyamin; Febrina Dian, Kurniasari; Reza Pahlevi, Munirwan; Putra Jaya, Ramadhansyah (Hindawi, 2022)
The increasing use of concrete in construction has caused an increase in the need for resources for concrete mixtures and driving wide-scale mining. One alternate material that can be used for aggregates replacement is coral. Coral aggregates (CA) have similar chemical characteristics to cement. The compressive strength and tensile splitting strength tests of concrete coral aggregates were performed based on the ASTM and ACI standards. This study aims are to investigate the usage of CA as a partial replacement of cement and fine aggregate to increase the strength of concrete at substitution percentages of 0, 5, 10, and 15%. Two different water submerged scenarios of distilled water and salt sea water immersion were applied. The concrete strength test was carried out after 28 days of curing time, with the specified concrete quality of 17 MPa. The results showed that immersion in distilled water has a higher concrete strength than immersion in sea water. The maximum compressive strength of concrete for distilled and sea water immersion is for 0% CA content of 18.47 and 14.89 MPa, respectively. Moreover, the highest value of the split tensile strength of concrete with distilled and sea water immersion is for CA substitution of 5% of 2.52 and 2.5 MPa, respectively. The addition of 5% coral aggregates to cement and fine sand is the optimum combination since it increases the maximum split tensile strength of concrete.